China's growth the making of an economic superpower - Yueh, Linda Y. (Linda Yi-Chuang) (Oxford, United Kingdom Oxford University Press, 2013)
"China's economic growth has transformed the country from one of the poorest in the world to its second largest economy. Understanding the drivers of growth remains elusive as the country is affected by both its transition from central planning and the challenges of a developing country. This book examines the main themes of growth, offering micro level evidence to shed light on the macro drivers of the economy. It also focuses on law and informal institutions of the economy to highlight the importance of entrepreneurship and the development of the private sector." -- Publisher's description.
1. Introduction -- 2. New growth theories : transition and institutional change -- 3. Neoclassical growth : labour productivity and corporate restructuring -- 4. Endogenous growth : human capital and labour market reforms -- 5. 'Catch-up' growth : technology transfers and innovation -- 6. Informal growth determinants : self-employment and social capital. -- 7. Financial and legal development : the role of private enterprises in growth -- 8. Global integration and growth : rebalancing the economy -- 9. Conclusion : the role of the state.
Includes bibliographical references (pages 321-339) and index.
Keywords: Economic development -- China -- History -- 21st century; China -- Economic conditions -- 1976-2000.; China -- Economic conditions -- 2000- .